A PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN PERUMAHAN DENGAN METODE ADDITIVE RATIO ASSESSMENT (ARAS) BERBASIS WEB: DESIGN OF A DECISION SUPPORT SYSTEM FOR HOUSING CHOICE USING THE WEB-BASED ADDITIVE RATIO ASSESSMENT (ARAS) METHOD - fabio junior; R.Wahyud Darmawan; Septa Petriyansyah (Universitas Tangerang Raya, 2025)
Population growth in Indonesia continues to increase, making the need for houses as a place to live also increasing. The current large number of housing complexes with various criteria and their respective advantages makes prospective buyers quite confused about choosing the right and suitable housing for their residence. This research aims to provide recommendations for suitable housing for prospective buyers through a decision support system using the Additive Ratio Assessment (ARAS) Method based on calculations from Criteria Data, Sub-Criteria Data and Alternative Assessment Data. The recommendations given are in the form of a ranking where the housing alternative with the highest degree of utility value is the most recommended alternative. In this research, there are 5 (five) Data Criteria required by prospective buyers, namely Price, Location, Accessibility, Facilities and Environmental Safety. Then there are 5 (five) housing alternatives, namely Batara Parkview, Batara Village, Kota Batara, Triraksa Village 2 and Kota Cakra. The results of the decision support system calculations using the Additive Ratio Assessment (ARAS) method produce (1) Kota Cakra as the most recommended housing, then (2) Triraksa Village 2, (3) Batara Parkview, (4) Batara Village and (5) Kota Batara.Keywords: Housing Selection, Additive Ratio Assessment (ARAS) Method, Decision Support Systems